(untitled) (Ameghiniana, 2013)
The author makes a revision of the platispermic seeds illustrated by Kurtz (1921). The finding of the original manuscript and the specimens of the Kurtz’s Collection, lost for more than 50 years, permitted the enlightening of one oí the problems concerning the use of the genus Rhipidopsis which is applied in his work, both to leaf and seed impressions. The review of the material, enabled to confirm the absence of organic conection between leaves and seeds. This is the reason why both elements must be identified with their own generic and specific terms. Despite the evident mistake in handling his data, Kurtz’s idea was honored. The author makes a morphological study of the seeds, describes the material, gives a diagnosis, encloses all the seeds ilustrated under the genus Samaropsis and introduces a new species; Samaropsis kurtzii sp. nov.